A framework for the development of marketing strategies at Goldfields Casino - De Beer, Dennis (University of the Free State, 2014)
The objective of this field study was to investigate the effectiveness of the formulation and implementation of marketing strategy at business and functional level within a given organisation. The work was prompted by a need to assess and address the framework for developing marketing strategy at different tiers of decision making at different levels within one organisation consisting of multiple brands. The investigation further sought to determine whether formulated strategy can influence business more than current environmental challenges. The work took cognisance of the organisational structure, the line of business, the business and marketing strategies deployed at different levels within the group, and the specific macro environmental factors within which the industry operates. The qualitative method employed relied on structured interviews, the content of which was utilised to obtain information and analyse the current practice within the organisation against the academic theory. The overarching findings confirmed the interrelatedness and interdependence of strategy throughout all levels within an organisation. The findings supported the importance of marketing strategy as a major function of overall business strategy. Furthermore, the function linked the business with its environment. With regard to the specific case study, the findings also suggest that: - there might be uncertainty and different interpretations within organisations at different levels with regard to responsibilities in the strategy processes; - there might be a shortfall in information and expertise required to formulate marketing strategy; and - there might be a partial breakdown in communication between different levels within the organisation’s hierarchy which hamper the implementation of strategy and which, in turn, makes the chosen strategies less effective.
Dissertation (MBA (Business Administration))--University of the Free State, 2014
Keywords: Strategy; Corporate strategy; Business strategy; Functional strategy; Marketing strategy; Interrelatedness; Marketing planning; Marketing process; Casino industry; Casinos -- South Africa -- Welkom; Interdependence